PERBEDAAN EFEKTIFITAS FILM ANIMASI DAN FILM CERITA TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP ANAK TENTANG KESEHATAN GIGI - Isha Sandya; Sri Widati (Universitas Airlangga, 2019)
According to Basic Health Research 2013 states that the age group less than 12 years ie age 5-9 years 28.9% suffered dental caries. The aim of this study is to analyze the effectiveness of animated movies and non- animated movies in improving children’s knowledge and behavior concerning dental health. This study was designed based on quasi experimental design. The samples of this study were the students of Class 3A and Class 3B SDN 03 Kepanjen consisting of 63 students. The independent variables of this study were animated movie and non-animated movie concerning dental health while the dependent variables were children’s knowledge and behavior. The collected data were analyzed using Mann Whitney test. The findings of this study show that the respondents are aged between 8 and 10 years old. There is difference in terms of knowledge before and after the students received intervention through animated movie and non-animated movie. Animated movie seems to be more effective in improving the respondents’ knowledge to maintain dental health than non-animated movie as indicated by the average score for animated movie intervention is higher than non-animated movie intervention.